2004
DOI: 10.1002/humu.20083
|View full text |Cite
|
Sign up to set email alerts
|

The CDKN2A database: Integrating allelic variants with evolution, structure, function, and disease association

Abstract: In this report, we introduce the CDKN2A Database, an online database of germline and somatic variants of the CDKN2A tumor suppressor gene recorded in human disease through the year 2002, annotated with evolutionary, structural, and functional information. The CDKN2A Database improves upon existing resources by: 1) including both somatic mutations and germline variants, thereby adding the perspective of somatic cell carcinogenesis to that of hereditary cancer predisposition; 2) including information that assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…As noted in previous reports [Murphy et al, 2004], there has been significant variability between authors regarding mutation nomenclature for mutations at certain gene loci; standardization was imperative for meaningful analysis. Included in Supplementary …”
Section: Data Extractionmentioning
confidence: 95%
See 1 more Smart Citation
“…As noted in previous reports [Murphy et al, 2004], there has been significant variability between authors regarding mutation nomenclature for mutations at certain gene loci; standardization was imperative for meaningful analysis. Included in Supplementary …”
Section: Data Extractionmentioning
confidence: 95%
“…We used the LSDBs for TP53 [Olivier et al, 2002] and CDKN2A [Murphy et al, 2004] and analyzed our UVB-signature rates at these two loci relative to non-skin cancers (NSCs; defined as cancers in the locus-specific databases (LSDBs) arising from tissue other than ''SKIN,'' and ''HEAD & NECK'') and another non-melanoma skin cancer, cutaneous squamous cell carcinomas (SCCs). Uncultured cutaneous melanomas had a greater percentage of UVB-signature mutations (Fig.…”
Section: Comparison Of Uvb-signature Mutations Between Melanoma and Omentioning
confidence: 99%
“…The small region (<42kb in Hapmap II) including p16 INK4a / ARF and p15 INK4b is amongst the most frequent lost in human cancer (Kim and Sharpless, 2006) and germline mutations of p16 INK4a /ARF are linked to melanoma and other malignancies (Murphy et al, 2004;Lang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This is happening because it is acknowledged that curation of mutations in genes is best done by experts in that gene or disease [Cotton, 2000], rather than by workers at central databases who collect information from the literature. This notion has been underscored recently by Gout et al [2007], who, using their expertise as LSDB curators, documented 5% errors in the literature, and Murphy et al [2004] found that 43% of CDKN2A mutations had at least one error in the report. Obviously, these errors cannot be tolerated since serious decisions, such as abortion and radical therapy, are being made on published data.…”
Section: Introductionmentioning
confidence: 98%